The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnbeh.2021.646528
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Change of Lymphocyte-to-Monocyte Is Associated With the Occurrence of POCD After Cardiovascular Surgery: A Prospective Observational Study

Abstract: Objective: Postoperative cognitive dysfunction (POCD) is a common and severe complication of cardiovascular surgery. Lymphocyte-to-monocyte ratio (LMR) has been reported to be an independent predictor of lots of diseases associated with inflammation, but the association between the LMR and POCD is not clear. The present study aimed to investigate the potential value of LMR level to predict POCD in patients undergoing cardiovascular surgery.Methods: A prospective observational study was performed on the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…On the other hand, anesthesia may harm cognitive function by different drugs, methods, and depth [ 54 56 ]. In addition, the scores of PND patients were mainly decreased in word short-term recall, delayed recall, and delayed interference tests, indicating their neurocognitive damage were basically in aspects of short-term and delayed memory, almost consistent with that of the previous study [ 2 ]. Besides, we compared the baseline information and blood examinations between the mild PND group and severe PND group that no significant difference was displayed.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, anesthesia may harm cognitive function by different drugs, methods, and depth [ 54 56 ]. In addition, the scores of PND patients were mainly decreased in word short-term recall, delayed recall, and delayed interference tests, indicating their neurocognitive damage were basically in aspects of short-term and delayed memory, almost consistent with that of the previous study [ 2 ]. Besides, we compared the baseline information and blood examinations between the mild PND group and severe PND group that no significant difference was displayed.…”
Section: Discussionsupporting
confidence: 88%
“…This concept combines the postoperative delirium (POD) and postoperative cognitive dysfunction (POCD). At the same time, POD is defined as an acute disorder of attention and cognition after surgery, and POCD used to be a concept but not a clinical diagnosis, representing a significant decline in neurocognitive performance in attention, orientation, memory, verbal fluency, coordination and so on [ 2 , 3 ]. PND has been proved to increase the cost of care, reduce the quality of life, increase the risk of long-term cognitive decline and mortality [ 4 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, most of the studies investigated POCD over a very short period of time (such as 3, 5, 6 and 7 days after surgery). 23,25,28,[32][33][34]37,40,41 Therefore, the results may be directly affected by practice effects, medications (such as opioids), symptoms such as pain and other acute mental conditions such as delirium. Only two studies 21,33 reported postoperative delirium, and just one 21 reported that delirium is a risk factor for POCD.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies excluded females only. 20,21 Regarding the type of surgery, 17 studies (73.9%) reported openheart cardiopulmonary bypass (CPB), [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] two studies (8.6%) noted off-pump coronary artery bypass (OPCAB) 37,38 and two studies (8.6%) reported both OPCAB and CPB. 20,29 Two studies (8.6%) did not report the type of surgical technique.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Общая анестезия, по сравнению с регионарной (либо сочетанной), существенно повышает риск когнитивных нарушений [35,36]. Значительно возрастает риск развития когнитивных нарушений при реконструктивной сосудистой хирургии сонных артерий, кардиохирургии [37], особенно с использованием искусственного кровообращения. В исследованиях Т. В. Клыпа [38,39] показано развитие нейрокогнитивных нарушений различной степени тяжести у 30-70% больных после кардиохирургических вмешательств.…”
Section: этиологияunclassified